African growth miracle or statistical tragedy? Interpreting trends in the data over the past two decades - Morten Jerven (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper reviews the current problems of national accounting in Sub-Saharan Africa. With the current uneven application of methods and availability of data, any ranking of countries according to gross domestic product levels is misleading. It is increasingly acknowledged that the problems associated with national accounts in Africa may have caused growth to be underestimated, and there are concerns that gross domestic product does not capture or cohere with concurrent trends on poverty and wealth from other surveys. It is argued that this varies from country to country, and that in some countries current wealth is underestimated, whereas in others recent growth is overestimated.
Keywords: E01; N17; 330; economic growth; national income accounting; Sub-Saharan Africa